Effect of electromagnetic field on whole blood, biochemical and hormone level in human - AKPOLAT, Veysi; YAVAŞ, Mehmet Cihan; GÖRGÜLÜ, Özkan; KAPLAN, İbrahim (Jurnal Teknologi Laboratorium, 2019)
The electromagnetic field is increasing in our environment and these exposures cause concern. The aim of our study is to investigate the effects of magnetic fields generated by the hairdryer devices used by women working in the same job on their serum biochemistry, whole blood, and hormone values. The sixteen women working continuously in hairdressing salons were included in the study. Two groups of studies were designed: control (n:8, mean age: 22.25±6.04) and experimental group (n:8, mean age:23,62±6.67). The biochemical (median values of alanine aminotransferase, aspartate aminotransferase, triglycerides, and very-low-density lipoprotein were found high) and hormonal results of the experimental group were compared with the biochemical (cholesterol, low-density lipoprotein, and very high-density lipoprotein had high median values) and hormonal results of the control group and no significant difference was found (p>0.05). When the whole blood parameters were examined, the white blood cells and mean platelet volume results of the experimental group were significant (p<0.05), while there was a meaningless difference between red blood cell, hemoglobin, hematocrit, mean corpuscular volume, red cell distribution width and platelet values (p>0.05). It is evident from the results that occupational exposure to magnetic fields constantly leads to changes in the biochemistry, hormone and whole blood parameters of the female.